A coincident indicator of the Gulf Cooperation Council (GCC) business cycle - Al-Hassan, Abdullah (IMF working paper, 2009)
This paper constructs a coincident indicator for the Gulf Cooperation Council (GCC) area business cycle. The resulting coincident indicator provides a reliable measure of the GCC business cycle; over the last decade, the GCC coincident index and the real GDP growth have moved closely together. Since the indicator is constructed using a small number of common factors, the strong correlation between the indicator and real GDP growth points to a high degree of commonality across GCC economies. The timing and direction of movements in macroeconomic variables are characterized with respect to the c.